2015
DOI: 10.1371/journal.pone.0140242
|View full text |Cite
|
Sign up to set email alerts
|

A 1H NMR Investigation of the Interaction between Phenolic Acids Found in Mango (Manguifera indica cv Ataulfo) and Papaya (Carica papaya cv Maradol) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) Free Radicals

Abstract: The benefits of phenolic acids on human health are very often ascribed to their potential to counteract free radicals to provide antioxidant protection. This potential has been attributed to their acidic chemical structure, which possesses hydroxyl groups in different positions. Phenolic acids can interact between themselves and exhibit an additive, antagonistic or synergistic effect. In this paper, we used 1H NMR to analyze the interactions and mechanisms that are present in major phenolic acids found in mang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 22 publications
10
47
0
Order By: Relevance
“…This indicates that compounds I and II are the antidiabetic compounds in the EtOAc fraction of H. sabdariffa . H 1 and C 13 NMR data revealed that fractions I and II are protocatechuic acid and gallic acid, respectively (Figure ) (López‐Martínez, Santacruz‐Ortega, Navarro, Sotelo‐Mundo, & González‐Aguilar, ; Cen, Xiao, Chen, & Liu, ). Interestingly, earlier studies have also demonstrated the α‐amylase and α‐glucosidase inhibitory activities of these compounds (Oboh, Ogunsuyi, Ogunbadejo, & Adefegha, ).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that compounds I and II are the antidiabetic compounds in the EtOAc fraction of H. sabdariffa . H 1 and C 13 NMR data revealed that fractions I and II are protocatechuic acid and gallic acid, respectively (Figure ) (López‐Martínez, Santacruz‐Ortega, Navarro, Sotelo‐Mundo, & González‐Aguilar, ; Cen, Xiao, Chen, & Liu, ). Interestingly, earlier studies have also demonstrated the α‐amylase and α‐glucosidase inhibitory activities of these compounds (Oboh, Ogunsuyi, Ogunbadejo, & Adefegha, ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the peaks from 3 to 5 ppm in TA-DA spectrum are attributed to the protons on amines adjacent to the aromatic rings, suggesting the reaction between TA-DA. 52 Lastly, the disappearance of phenol proton peaks from 9 to 10 pm in TA-DA spectrum suggests the oxidation of phenol groups to quinone groups. It should be noted that tannic acid was not oxidized beforehand in the NMR sample preparation (whereas it is in the reaction with CNCs), which implies the addition of decylamine further induces the oxidation of tannic acid.…”
Section: Dispersion Of Modified Cncs In Non-polar Solventsmentioning
confidence: 97%
“…The bulk weight of dry chopped oat straw in these researches is (0,12±0,01) g/sm 3 on condition that the length of the used aggregates is 5 mm and aggregates are made by chopping the native raw materials on disagglomerator of rotary-cutting type. The calculation of the bulk weight was held in compliance with standard methods.…”
Section: Presentation Of the Main Research Materials (Methods And Objementioning
confidence: 99%
“…At the moment, a considerable number of scientifically-practical researches aimed at studying polyphenol component of numerous products of economic activity, such as wine [1], some agricultural products [2,3], and herbs, among which lists the oat, Avena Sativa, in its various natural and synthetic forms, are known. Polyphenols of the vegetative nature are represented by a variety of forms that potentially anticipates a wide range of non-specific and specific biological activity, and actualizes its further research and application in the medical practice [4,5].…”
Section: Introductionmentioning
confidence: 99%